The effect of service concept on customer acquisition: the moderating role of manager’s experience on Savings and Credit Cooperative Societies in Tanzania - Flora Antony; Victoria Makuya; Ruth Elias (LBS Journal of Management & Research)
Purpose – This study aims to investigate the influence of the service concept on customer acquisition and when the relationship is moderated with manager’s experience in Savings and Credit Cooperative Societies (SACCOS) within Dar es Salaam City, Tanzania. Design/methodology/approach – The study adopts a cross-sectional research design and utilizes simple random sampling to select 226 respondents, all of whom are managers of SACCOS in Tanzania. Data were collected through a questionnaire and analyzed using a partial least square structural equation modeling (PLS-SEM). Findings – The findings indicate that service concept have a highly statistically significant impact on customer acquisition, with a p-value of less than 0.05. Conversely, managers’ experience also influences customer acquisition by the p-value of less than 0.05. The result also confirms the significance influence of positive moderating effect of manager’s experience on the relationship between service concept and customer acquisition, with a p-value of less than 0.05, therefore it shows that manager’s experience facilitate the influence of service concept to customer acquisition. Practical implications – The findings of this study provide valuable insights for SACCOS aiming to thrive and attract more customers. By understanding the nuances of service concepts, these institutions can refine their strategies for customer acquisition effectively. Originality/value – The study’s insights into the composite effect of service concepts hold significance for SACCOS seeking to enhance their customer acquisition strategies enhanced by manager’s experience. These findings contribute new perspectives to the SACCOS and other related financial services sector, offering fresh insights into innovation and customer-centric approaches.